Acquisition of scientific literature in developing countries - Taib, Rosna (SAGE Publications, 1989)

(untitled)
The second of a series of articles on the acquisition of scientific literature by libraries in developing countries. Deals mainly with higher education libraries. Summarizes the Malaysian background and the relationship between scientific research and libraries in Malaysia. Describes government policies with regard to contract purchasing, copyright and the national language and their effects on library acquisitions. Discusses acquisitions policy, the selection process, the acquisition of journals, audio-visual materials, maps and related materials, conference papers and theses, the role of gifts and exchanges in acquisitions work and problems of customs clearance and censorship. Progress in cooperative acquisitions and the automation of acquisitions work are also described. Presents proposals for further action.